2016
DOI: 10.2298/vsp140508001d
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of breast ultrasound in mammography BI-RADS 0 and clinically indeterminate or suspicious of malignancy breast lesions

Abstract: Ultrasonography BI-RADS improved classification of breast masses. The ultrasound BI-RADS 4 (A, B, C) and BI-RADS 5 lesions should be worked-up with biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…According to the latest research, cancer microcalcifications are observed in 70% of cases by new US instruments . Although 66.9% of DCIS cases showed microcalcification on US images in this study, significant differences were found in DCIS and FA cases; however, not all of the grayscale US parameters showed significant differences.…”
Section: Discussioncontrasting
confidence: 59%
“…According to the latest research, cancer microcalcifications are observed in 70% of cases by new US instruments . Although 66.9% of DCIS cases showed microcalcification on US images in this study, significant differences were found in DCIS and FA cases; however, not all of the grayscale US parameters showed significant differences.…”
Section: Discussioncontrasting
confidence: 59%
“…This is because the sensitivity of mammography decreases as the density of glandular breast tissue increases, and ultrasound is more sensitive at lower densities. 10,11 When it comes to ultrasound descriptors based on published research, the criterion of tumour change orientation has the best level of impartiality and agreement among the numerous clinicians doing the examination. Shape, surrounding tissue, and posterior phenomena are in the middle of the spectrum between the two extremes in terms of agreement, while change contour and its echogenicity (nonechogenic and hyperechogenic are benign, while hypoechogenic, isoechogenic changes, and complex lesions can be seen in both types of changes, but they are more suspicious of malignant nature) are the two areas where there is the least agreement.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms for this disease are abnormal vaginal bleeding and irregular menstrual cycles 1 . Regarding the usage of ultrasonography in making a diagnosis, there are no specific guidelines which would be used as a basis for suspecting this type of the tumor 7,8 . Uterus is the most common primary location of ETT (40%) as well as endocervix (31%).…”
Section: Discussionmentioning
confidence: 99%